1975
DOI: 10.1212/wnl.25.6.580
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous infarction in pituitary tumors

Abstract: In addition to progressive endocrine dysfunction and progressive visual loss, pituitary neoplasms may annouce their presence by the more catastrophic alternative of spontaneous tumor infarction. In two patients reported, illness due to the spontaneous infraction of pituitary tumors was heralded by sudden onset of focal headache associated with diplopia. Stupor, confusion, and evidence of increased intracranial pressure occurred without subarachnoid hemorrhage or massive extrasellar extension of tumor. One pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…35 This term has also been used to refer to the sudden infarction of non-tumorous pituitary glands. 36 The incidence of pituitary apoplexy varies from 0.6% to 22%, depending on the definition used. 17 If pathological evidence of hemorrhage into pituitary adenomas is taken as the criterion for diagnosis of pituitary apoplexy, then the incidence may vary from 16% to 22%.…”
Section: Discussionmentioning
confidence: 99%
“…35 This term has also been used to refer to the sudden infarction of non-tumorous pituitary glands. 36 The incidence of pituitary apoplexy varies from 0.6% to 22%, depending on the definition used. 17 If pathological evidence of hemorrhage into pituitary adenomas is taken as the criterion for diagnosis of pituitary apoplexy, then the incidence may vary from 16% to 22%.…”
Section: Discussionmentioning
confidence: 99%
“…However, we now know that ischemic or hemorrhagic necrosis of a pituitary tumor may be entirely silent and is more com mon than classical apoplexy [7,8] and that it may result in spontaneous regression of the tumor or the associated endocrinopathy [11][12][13]. It is only recently recognised that necrosis of the pituitary tumor occurs far more fre quently than anticipated and that the clinical presenta tions can be highly variable [3,5,7,8], Recurrent bleed ing, although well documented, [1,4], is thought to be uncommon [14], Our results suggest that this is not the case as the CT scan and histological findings suggest that recurrent episodes of bleeding is likely to be the rule rather than the exception. Six patients had CT changes indicative of both acute and chronic bleeding and 6 of the 8 surgically treated patients had hemosiderin deposi tion and fibrosis indicative of past bleeding in addition to the acute episode.…”
Section: Discussionmentioning
confidence: 99%
“…This can be due to a hemorrhage [1,2] or an extensive tumor infarction [3,4]. Little is known about the long term outcome of patients who have experienced apo plexy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once infarction has occurred, the tumour undergoes haemorrhagic necrosis which expands beyond the size of the original adenoma. However, these ex¬ planations may not be correct, since acute necrotic changes also occur in slow-growing pituitary ade¬ nomas (Conomy et al 1975) as in the present cases and recent angiographie studies have shown that pituitary adenomas may receive their blood supply directly from capsular arteries (Baker 1972 Bromocriptine has a direct action on pituitary adenoma cells of acromegaly to suppress GH re¬ lease (Ishibashi & Yamaji 1978). Its possible antitumour effect is supported by the observation that bromocriptine therapy improved visual field defi¬ cits in acromegalic patients (Wass et al 1977(Wass et al , 1979 as in those with a prolactin-secreting adenoma (Corenblum et al 1975;McGregor et al 1979a,b;George et al 1979;Landolt et al 1979).…”
Section: Discussionmentioning
confidence: 99%